2021
DOI: 10.1093/jjco/hyab075
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel mRNA signature for predicting early relapse in non-small cell lung cancer

Abstract: Background Recurrence after initial primary resection is still a major and ultimate cause of death for non-small cell lung cancer patients. We attempted to build an early recurrence associated gene signature to improve prognostic prediction of non-small cell lung cancer. Methods Propensity score matching was conducted between patients in early relapse group and long-term survival group from The Cancer Genome Atlas training se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Chiba et al found that CLEC7A could promote natural killer cells to secrete cytotoxic factors and thus fight lung cancer through cell-to-cell contact ( Chiba et al, 2014 ). In this study, CLEC7A had a positive effect on the prognosis of LUAD patients, which was consistent with the findings of previous studies ( Zou et al, 2020 ; Zhou et al, 2021b ; Lin et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Chiba et al found that CLEC7A could promote natural killer cells to secrete cytotoxic factors and thus fight lung cancer through cell-to-cell contact ( Chiba et al, 2014 ). In this study, CLEC7A had a positive effect on the prognosis of LUAD patients, which was consistent with the findings of previous studies ( Zou et al, 2020 ; Zhou et al, 2021b ; Lin et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%